Informal Learning and WTO Renewal Using Thematic Sessions to Create More Opportunities for Dialogue. (28th April 2021) - Wolfe, Robert
Abstract: 'Thematic sessions' bring dynamism to WTO by allowing committees to consider what works well under an agreement, including sharing experiences with implementation, what is not working, and what is next on the agenda. Thematic sessions are a broad class of meetings that are sponsored by or associated with a WTO body in some way, but that are not part of its formal meetings. The WTO held over 100 such sessions in the three years from 2017 to 2019. We found variation in how meetings are organized, which is related to the type of session, and we found variation in how themes are chosen, participation (who speaks), the degree of transparency, and funding. Comprehensive improvement is needed: some committees never hold thematic sessions, participation by capital‐based officials from developing countries is uneven, and too few sessions have a forward‐looking agenda. Enhanced use of thematic sessions can contribute to strengthening the pipeline between Geneva and capitals, and to better understanding in Geneva of what is happening on the ground. Abstract : "Thematic sessions" bring dynamism to WTO by allowing committees to consider what works well under an agreement, including sharing experiences with implementation, what is not working, and what is next on the agenda. Comprehensive improvement is needed: some committees never hold thematic sessions, participation by capital‐based officials and stakeholders from developing countries is uneven, and too few sessions have a forward‐looking agenda.